Research trends in the orthopedic surgical management of cerebral palsy: a cross-analytical study of publications in the past decade - Maher Ghandour; Matthias Klotz; Axel Horsch (Frontiers in Neurology, 2023)
Little is known about the trends in orthopedic surgical management of cerebral palsy (CP). In this cross-analytical study we examined alterations in research publications in this field in the past 10 years through four databases. Thus, we divided publications into old (2012–2017) and recent (2018–2022). To determine if the focus of research in this field has changed, we compared both periods based on publication’s (authors’ number, journal, country, design), patients’ (number, gender, age, CP type), and surgery-related (indication, number, category, type) characteristics. Publications showed a positive trend over the past 10 years with a peak in 2020. The number of publications was similar between old and recent ones (47.58% vs. 52.42%). Most research outputs were from the United States and Germany. Differences were noted between recent and old publications regarding journals (p = 0.0001), journal category (p = 0.023), authors’ number (p = 0.006), and patients’ age (p = 0.02). The impact factor was also different (p = 0.0001). However, no differences were noted regarding other characteristics (p > 0.05). The research output regarding surgical orthopedic management in CP has increased in the past decade with no difference between 2012–2017 and 2018–2022. Except for the number of authors, journal name, and patients’ age, no significant differences were noted between both periods.